Avaliação de implantes osseointegráveis em carga imediata em maxilas reconstruídas com enxerto de crista ilíaca - Sato, Henrique Kunio (2007)
PURPOSE: The present study evaluated the oral reabilitation systems with immediate loading of implants in patients with severely atrophic maxilla, whose were previous treated with autogenous bone graft from iliac crest bone. MATERIAL AND METHODS: 10 patients, 2 male and 8 female, that were submitted to total reconstruction of the maxilla with inlay (sinus lift) and onlay grafting for vertical augmentation, were treated with endosseous implants and fixed prostheses. Following a 4-month period after the grafting, the patients received 8-10 implants, a part of it was immediately loaded and another part was submerged during 6 month for posterior activation. Due to the insertion torque, the sample was divided in two groups, one which 6 implants were loaded in strategic position, and the other which all implants were submerged. Overall, 30 implants were loaded and 63 implants remained without function. Clinic analysis were achieved to verify the stability of the fixtures, with resonance frequency analysis (RFA) and assessment of marginal bone loss across standard periapical radiographs. RESULTS: In general, the immediately loaded implant cumulative survival rate was 80% and survival rate of submerged implants was 94%. As regards the stability measurements, initial RFA and after 6 month did not show statistically significant difference (p=0,05). The level of marginal bone loss was a mean of -1,6mm. CONCLUSION: Therefore, the maxillary implant reconstruction, specially where there are atrophic reduction of the alveolar process of the maxilla, the risk of implants failures is high. In these cases, due to the reconstruction area, the primary stability of the implants is difficult to gain, reducing the dental implant placement on immediate load. Nevertheless, procedures with two stages seems to provide more predictability and high implants survival rate.